Pasteurization of food by hydrostatic high pressure: chemical aspects - Tauscher, Bernhard (Zeitschrift für Lebensmittel-Untersuchung und -Forschung. A, European food research, 1995)
Food pasteurized by hydrostatic high pressure have already been marketed in Japan. There is great interest in this method also in Europe and USA. Temperature and pressure are the essential parameters influencing the state of substances including foods. While the influence of temperature on food has been extensively investigated, effects of pressure, also in combination with temperature, are attracting increasing scientific attention now. Processes and reactions in food governed by Le Chatelier's principle are of special interest; they include chemical reactions of both low- and macromolecular compounds. Theoretical fundamentals and examples of pressure affected reactions are presented.
Gesehen am 15.01.2026